新谣 ：我们的心声 = Xinyao : our voice - Low, Charlotte Qian Hui (Nanyang Technological University, 2020)
Inspired by my past encounters with Xinyao, 新谣: 我们的心声 (Xinyao: Our Voice) is a semi-bilingual memory-cum-lyric book project that highlights the main aspects of Xinyao: The songs reflecting the everyday life, candid feelings and experiences about friendship, love, family, life and more of college youths who wrote them primarily in the 1980s. This book, which takes on a journal-like editorial look, features a selection of ten classic Xinyao which I resonate with and my personal anecdotes in relation to each song. In addition the book features a series of illustrations, each inspired from the lyrics to bring the stories told in the songs to life. By experiencing Xinyao vicariously from my personal sharing, I hope that one will find a connection with the music through nostalgia, know about it a little more and gain interest in it which in turn would allow for a continued preservation of the music.